Cold Shock Induced Protein RBM3 but Not Mild Hypothermia Protects Human SH-SY5Y Neuroblastoma Cells From MPP+-Induced Neurotoxicity - Yang, Hai-Jie; Shi, Xiang; Ju, Fei; Hao, Bei-Ning; Ma, Shuang-Ping; Wang, Lei; Cheng, Bin-Feng; Wang, Mian (Frontiers in Neuroscience, 2018)
The cold shock protein RBM3 can mediate mild hypothermia-related protection in neurodegeneration such as Alzheimer’s disease. However, it remains unclear whether RBM3 and mild hypothermia provide same protection in model of Parkinson’s disease (PD), the second most common neurodegenerative disorder. In this study, human SH-SY5Y neuroblastoma cells subjected to insult by 1-methyl-4-phenylpyridinium (MPP+) served as an in-vitro model of PD. Mild hypothermia (32°C) aggravated MPP+-induced apoptosis, which was boosted when RBM3 was silenced by siRNA. In contrast, overexpression of RBM3 significantly reduced this apoptosis. MPP+ treatment downregulated the expression of RBM3 both endogenously and exogenously and suppressed its induction by mild hypothermia (32°C). In conclusion, our data suggest that cold shock protein RBM3 provides neuroprotection in a cell model of PD, suggesting that RBM3 induction may be a suitable strategy for PD therapy. However, mild hypothermia exacerbates MPP+-induced apoptosis even that RBM3 could be synthesized during mild hypothermia.